Networks and product innovation across European SMEs - Nadine Behncke (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2015)
This paper analyzes the effect of different cooperation forms on innovation in small and medium enterprises in Belgium, Germany, Portugal and Spain using Community Innovation Survey data from 2008. We find that vertical cooperation and knowledge cooperation increases the probability to introduce product innovations in all countries. The positive effect is driven by cooperation in the home country in Germany and Spain while it comes from cooperations with foreign countries in Belgium and Portugal. However, our results suggest that SME are not able to capitalize from these cooperations. We find a significant and positive effect of horizontal cooperation on sales due to product innovation only in Germany.
Keywords: L14; L25; L2; 330; networks; SMEs; innovation